Mapping the primary structure of copper/topaquinone-containing methylamine oxidase from Aspergillus niger - Lenobel, R; Sebela, M; Frébort, I (Folia microbiologica, 2005)
The amino acid sequence of methylamine oxidase (MeAO) from the fungus Aspergillus niger was analyzed using mass spectrometry (MS). First, MeAO was characterized by an accurate molar mass of 72.4 kDa of the monomer measured using MALDI-TOF-MS and by a pI value of 5.8 determined by isoelectric focusing. MALDI-TOF-MS revealed a clear peptide mass fingerprint after tryptic digestion, which did not provide any relevant hit when searched against a nonredundant protein database and was different from that of A. niger amine oxidase AO-I. Tandem mass spectrometry with electrospray ionization coupled to liquid chromatography allowed unambiguous reading of six peptide sequences (11-19 amino acids) and seven sequence tags (4-15 amino acids), which were used for MS BLAST homology searching. MeAO was found to be largely homologous to a hypothetical protein AN7641.2 (EMBL/GenBank protein-accession code EAA61827) from Aspergillus nidulans FGSC A4 with a theoretical molar mass of 76.46 kDa and pI 6.14, which belongs to the superfamily of copper amine oxidases. The protein AN7641.2 is only little homologous to the amine oxidase AO-I (32% identity, 49 % similarity).
Keywords: Chromatography, Liquid; sekvenční homologie aminokyselin; Sequence Homology, Amino Acid; Peptide Mapping; Copper; Molecular Sequence Data; molekulová hmotnost; Sequence Analysis, Protein; molekulární sekvence - údaje; Molecular Weight; sekvenční analýza proteinů; výpočetní biologie; Aspergillus niger; peptidové mapování; Oxidoreductases Acting on CH-NH Group Donors; Trypsin; měď; dihydroxyfenylalanin; hmotnostní spektrometrie s elektrosprejovou ionizací; Amino Acid Sequence; Computational Biology; izoelektrický bod; chromatografie kapalinová; isoelektrická fokusace; spektrometrie hmotnostní - ionizace laserem za účasti matrice; oxidoreduktasy působící na CH-NH vazby; Isoelectric Focusing; Isoelectric Point; Spectrometry, Mass, Electrospray Ionization; trypsin; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; sekvence aminokyselin; Dihydroxyphenylalanine